Antihyperglycemic Effect of Ginsenoside Rh2 by Inducing Islet β-cell Regeneration in Mice - Wang, Y.; Wang, H.; Liu, Y.; Li, C.; Qi, P.; Bao, J. (Hormone and Metabolic Research, 2012)
The present study was designed to determine the antihyperglycemic function of ginsenoside Rh2 (GS-Rh2) by the regeneration of β-cells in mice that underwent 70% partial pancreatectomy (PPx), and to explore the mechanisms of GS-Rh2-induced β-cell proliferation. Adult C57BL/6J mice were subjected to PPx or a sham operation. Within 14 days post-PPx, mice that underwent PPx received GS-Rh2 (1 mg/kg body weight) or saline injection. GS-Rh2-treated mice exhibited an improved glycemia and glucose tolerance, an increased serum insulin levels, and β-cell hyperplasia. Meanwhile, increased β-cell proliferation percentages and decreased β-cell apoptosis percentages were also observed in GS-Rh2-treated mice. Further studies on the Akt/Foxo1/PDX-1 signaling pathway revealed that GS-Rh2 probably induced β-cell proliferation via activation of Akt and PDX-1 and inactivation of Foxo1. Studies on the abundance and activity of cell cycle proteins suggested that GS-Rh2-induced β-cell proliferation may ultimately be achieved through the regulation of cell cycle proteins. These findings demonstrate that GS-Rh2 administration could inhibit the tendency of apoptosis, and reverse the impaired β-cell growth potential by modulating Akt/Foxo1/PDX-1 signaling pathway and regulating cell cycle proteins. Induction of islet β-cell proliferation by GS-Rh2 suggests its therapeutic potential in the treatment of diabetes.
Keywords: islet regeneration; partial pancreatectomy; ginsenoside Rh2 (GS-Rh2); cyclin D-Cdk4 complex; Akt/Foxo1/PDX-1 signaling pathway